Architecture of Paradiplozoon homoion: A diplozoid monogenean exhibiting highly-developed equipment for ectoparasitism - Hodová, Iveta; Sonnek, Radim; Gelnar, Milan; Valigurová, Andrea (PloS one, 2018)
Diplozoidae (Monogenea) are blood-feeding freshwater fish gill ectoparasites with extraordinary body architecture and a unique sexual behaviour in which two larval worms fuse and transform into one functioning individual. In this study, we describe the body organisation of Paradiplozoon homoion adult stage using a combined approach of confocal laser scanning and electron microscopy, with emphasis on the forebody and hindbody. Special attention is given to structures involved in functional adaptation to ectoparasitism, i.e. host searching, attachment and feeding/metabolism. Our observations indicate clear adaptations for blood sucking, with a well-innervated mouth opening surrounded by sensory structures, prominent muscular buccal suckers and a pharynx. The buccal cavity surface is covered with numerous tegumentary digitations that increase the area in contact with host tissue and, subsequently, with its blood. The buccal suckers and the well-innervated haptor (with sclerotised clamps controlled by noticeable musculature) cooperate in attaching to and moving over the host. Putative gland cells accumulate in the region of apical circular structures, pharynx area and in the haptor middle region. Paired club-shaped sacs lying laterally to the pharynx might serve as secretory reservoirs. Furthermore, we were able to visualise the body wall musculature, including peripheral innervation, the distribution of uniciliated sensory structures essential for reception of external environmental information, and flame cells involved in excretion. Our results confirm in detail that P. homoion displays a range of sophisticated adaptations to an ectoparasitic life style, characteristic for diplozoid monogeneans.
Keywords: interakce hostitele a parazita; Platyhelminths; ploštěnci; Animals; Microscopy, Confocal; Microscopy, Electron, Scanning; Fishes; zvířata; ryby; infestace ektoparazity; Host-Parasite Interactions; Ectoparasitic Infestations; konfokální mikroskopie; mikroskopie elektronová rastrovací